2014
DOI: 10.5935/1678-9741.20140080
|View full text |Cite
|
Sign up to set email alerts
|

NEW TECHNIQUE "Right Anterior Small Thoracotomy (RAST operation) for grafting the Right Internal Thoracic Artery to the Posterior Descending Artery (RITA to PDA) on the beating heart in a third REDO CABG patient". A novel coronary technique.

Abstract: Third REDO-CABG is a challenge for the surgical team. Usually a patent mammary is the only graft working and the sternotomy becomes a risky procedure. Injury to a patent graft has been associated to a high mortality rate. Many different approaches have been proposed. We describe a novel technique to approach the right coronary artery through a right anterior small thoracotomy using the right mammary prolonged with saphenous vein for grafting the posterior descending artery on the beating heart. The technique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“… 3 However, to the best of our knowledge, there has been only one report of CABG using the RITA through a right thoracotomy. 4 Guida and colleagues 4 reported third-time redo CABG using the RITA through a right thoracotomy. However, the RITA needed to be extended with a saphenous vein graft to reach the posterior descending artery.…”
Section: Discussionmentioning
confidence: 99%
“… 3 However, to the best of our knowledge, there has been only one report of CABG using the RITA through a right thoracotomy. 4 Guida and colleagues 4 reported third-time redo CABG using the RITA through a right thoracotomy. However, the RITA needed to be extended with a saphenous vein graft to reach the posterior descending artery.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports of CABG via right thoracotomy, Guida et al 4 have reported a beating heart grafting technique through the right anterior small thoracotomy. Moreover, Mihos et al 5 have also reported simultaneous AVR and CABG for the right coronary artery via the right mini-thoracotomy approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports of CABG via right thoracotomy, Guida et al. 4 have reported a beating heart grafting technique through the right anterior small thoracotomy. Moreover, Mihos et al.…”
Section: Discussionmentioning
confidence: 99%